Characterization of Lasiodiplodia theobromae (B4d) isolated from kenaf seeds and its sensetivity towards diazotrophic bacteria - Madiha, Norhayati (2013)
Hibiscus cannabinus L. is commonly known as kenaf grows natively in east-central Africa and used in production of ropes, canvas, board making, oil absorption and animal feed. Kenaf is not only tolerant to many types of soil and other planting conditions; it is also resistant to pests and diseases. However, several diseases have been reported infecting the kenaf plant. Many studies were conducted on disease infected the leaves and roots but there is insufficient research effort to identify the causal agent of the disease on initial growth of kenaf causing loss of germination in seeds. The study was aimed to isolate and characterize the causal pathogen of seedborne disease on kenaf seed in Malaysia using morphological and molecular techniques and to confirm the pathogenicity. The second objective was to identify the potential diazotrophic bacteria in order to control the infection of seed-borne fungus. For isolation of the seed-borne fungus, the seed source was obtained from National Tobacco and Kenaf Board (LKTN) in Perlis. Twenty-one of fungal isolated from the seeds were obtained and tested for their pathogenicity. This study found that the fungus B4d showed highest isolation frequency and pathogenic to the seed. Morphological characterization of fungus B4d indicated that the colony was fast growing fungus. The conidia were dark brown in colour, two-celled, thin cell walled and oval shape with longitudinal striation when mature. In immature stage, the conidia were hyaline, smooth, single-celled and have thick cell walled. The average size of conidia was 24 μm (length) x 15 μm (width) while the average length/width ratio was 1.11 (n=50). The morphological findings described the fungus B4d as Lasiodiplodia theobromae. Identification of fungus B4d was also done through molecular characterization using 18S Internal Transcribed Spacer (ITS) regions of ribosomal deoxyribonucleic acid (rDNA). BLAST result indicated that the fungus was 100% similar to that of L. theobromae (JQ809341). Phylogenetic tree grouped the fungus in the same group with L. theobromae and distinct from other anamorph in the genus Botryosphaeria. The dual culture assay was conducted to determine diazotrophic bacteria that can suppress the L. theobromae growth. Among 61 bacterial strains isolated from kenaf roots, three strains were exhibited potent antagonistic effect against L. theobromae. Percentage inhibition radial growth (PIRG) values showed significant difference (P<0.05) on antagonism activity of the fungi. Three bacterial isolates recorded PIRG value more than 60% on L.theobromae. The highest PIRG value was shown by IRPP1b followed with RFC1a and RKBP3d, respectively. Selected diazotrophs have been identified. Molecular technique using 16S rDNA markers analysis confirmed the bacterial species were Burkholderia cepacia (JF820823), Burkholderia vietnamiensis (JF833110) and Bacillus subtilis (JF833115). Selected antagonistic bacteria were used in seed treatment in glasshouse. Treatments of seeds with diazotrophic bacterial suspension significantly reduced the infection of L.theobromae (P<0.05). This study showed that B. cepacia has more potential to reduce the fungal infection was 83% followed by B. vietnamiensis (78%) and B. subtilis (67%), respectively. The germination rate of kenaf seeds was increased by the time of inoculation with bacterial isolates. Therefore, B. cepacia, B. vietnamiensis and B. subtilis have a good potential in suppressing the growth of L.theobromae and increase the germination rate of kenaf seeds.